2020
DOI: 10.1002/smll.202001858
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Titanium Dioxide Nanoparticles Induce Stronger Adverse Effects in Obese Mice than Non‐Obese Mice: Gut Microbiota Dysbiosis, Colonic Inflammation, and Proteome Alterations

Abstract: The recent ban of titanium dioxide (TiO2) as a food additive (E171) in France intensified the controversy on safety of foodborne‐TiO2 nanoparticles (NPs). This study determines the biological effects of TiO2 NPs and TiO2 (E171) in obese and non‐obese mice. Oral consumption (0.1 wt% in diet for 8 weeks) of TiO2 (E171, 112 nm) and TiO2 NPs (33 nm) does not cause severe toxicity in mice, but significantly alters composition of gut microbiota, for example, increased abundance of Firmicutes phylum and decreased abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 68 publications
2
66
1
Order By: Relevance
“…Mu et al [ 38 ] reported that administration of TiO 2 NPs (10 and 50 nm) to young weaned mice for 2–3 months in the diet reduced the numbers of Bifidobacterium and Lactobacillus , which led to weight loss. In in vivo study conducted by Cao et al [ 11 ], oral administration of TiO 2 (E171, 112 nm) and TiO 2 NPs (33 nm) to obese and non-obese mice (0.1% w/w in the diet for 8 weeks) resulted in a significant reduction in the intestinal amounts of Bifidobacterium and Lactobacillus bacteria count number. The authors found that TiO 2 NPs induced more severe colon inflammation than TiO 2 (E171), especially in the more susceptible obese mice, which was also associated with their high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mu et al [ 38 ] reported that administration of TiO 2 NPs (10 and 50 nm) to young weaned mice for 2–3 months in the diet reduced the numbers of Bifidobacterium and Lactobacillus , which led to weight loss. In in vivo study conducted by Cao et al [ 11 ], oral administration of TiO 2 (E171, 112 nm) and TiO 2 NPs (33 nm) to obese and non-obese mice (0.1% w/w in the diet for 8 weeks) resulted in a significant reduction in the intestinal amounts of Bifidobacterium and Lactobacillus bacteria count number. The authors found that TiO 2 NPs induced more severe colon inflammation than TiO 2 (E171), especially in the more susceptible obese mice, which was also associated with their high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that TiO 2 NPs induced more severe colon inflammation than TiO 2 (E171), especially in the more susceptible obese mice, which was also associated with their high-fat diet. Authors suggested that TiO 2 exposure of mice with reduced levels of Bifidobacterium and Lactobacillus may result in increased susceptibility to such diseases as irritable bowel syndrome [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SiO 2 and TiO 2 nanoparticles can also induce cytotoxicity and thus may have a negative health impact. These studies have shown that SiO 2 and TiO 2 nanoparticles show toxicity in the human lung, intestinal cells and during in vivo experiments [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%